Сюжеты: сборник рассказов / Валерий Болтышев - Болтышев Валерий Александрович (Удмуртия, 1982)
Экземпляры: ЦБ/12/13/16/24/26 (20250128) / Инвентарный номер: 3536 / Цена: 0.30 / Сис.шифр: Р2 / Авт.знак: Б 79 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6